Sub-Millimeter-Wave 10 dB Directional Coupler Based on Micromachining Technique - Shuang Liu; Jiang Hu; Yong Zhang; Yupeng Liu; Tianhao Ren; Ruimin Xu; Quan Xue (International Journal of Antennas and Propagation)
A waveguide 10 dB directional coupler operating from 325 GHz to 400 GHz is designed based on the short-slot Riblet-type coupling configuration and fabricated using the deep reactive ion etching (DRIE) silicon micromachining technique. The skin depth and the conductivity of the gold film with the roughness of 0.2 μm are investigated at 300~1000 GHz frequency band for the higher accuracy. In order to measure the small-size four-port coupler using the two-port VNA with big-size flanges, three testing topologies are designed, in which the terahertz (THz) wedged-type absorbing material terminals are adopted as the waveguide matching loads. The measured average insertion loss is 0.5 dB after deducting the intrinsic loss and the measured average isolation is better than 25 dB, which are in good agreement with simulations. The analysis and the design are verified to be accurate and valuable for the high-performance sub-millimeter-wave waveguide components.